Evaluation of Low-Temperature Performance of Recycled Asphalt Mixture with Different Thermal History Reclaimed Asphalt Pavement - Chao Jin; Ya’nan Cui; Qileng Aori (Applied Sciences)
The utilization of reclaimed asphalt pavement (RAP) in asphalt mixtures not only reduces production costs and resource consumption but also provides significant environmental benefits. Consequently, technology and methodologies used for asphalt pavement recycling, aimed at enhancing the utilization rate of RAPs, have emerged as prominent topics in both academic research and engineering practice. Given the complex thermal history and poor low-temperature performance (LTP) of RAP, investigating the effects of varying thermal histories of RAPs on the LTP of a mixture holds substantial practical significance for increasing the utilization rate of RAP in seasonally frozen regions. In this study, scanning electron microscopy (SEM), the thermal stress restrained specimen test (TSRST), the trabecular bending test, and the bending beam creep test (BBCT) are utilized to examine the effects of the indoor simulation methods that produce RAPs with varying thermal histories and contents on a recycled asphalt mixture (RAM) from both microscopic and phenomenological perspectives. Additionally, this research investigates the accuracy of predicting the LTP of RAMs using the Burgers model. The test results indicate that the LTP of an RAM is influenced not only by the RAP content and its thermal history but also by the ambient temperature. Regardless of the thermal history of the RAP, the LTP of an RAM tends to decrease as the RAP content increases. Different thermal histories of RAPs exert varying effects on the low-temperature viscoelastic behavior of an RAM. The UVRAP reduces the viscoelastic temperature range of an RAM by an average of 10.79%, whereas the THRAP increases it by an average of 2.16%. These effects can be attributed to the distinct micromorphology of the asphalt on the surfaces of RAPs with a varying thermal history. Specifically, a greater number of micropores and microcracks on the asphalt surface leads to a poorer LTP of RAMs. Additionally, the residuals of the Burgers model for predicting the LTP of an RAM with THRAP exceeded −2. However, the Burgers model demonstrates predictive capabilities for evaluating the LTP of an RAM filled with RAP from the same source or with a similar thermal history.